2006
DOI: 10.3748/wjg.v12.i9.1412
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of paclitaxel in malignant ascites from advanced gastric cancer patients

Abstract: The concentration of paclitaxel in ascites is maintained within the optimal level for the treatment of cancer cells for up to 72 h after intravenous administration. Paclitaxel is a promising drug for the treatment of malignant ascites of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 19 publications
3
43
1
Order By: Relevance
“…The other patient, given 80 mg/m 2 of PTX, had serum PTX levels measured 168 h after PTX administration. In these two patient's, the plasma levels of PTX remained within the effective range for 60 and 72 h respectively [20]. These results together with those cited above [7,9,10], suggest that sequential chemotherapy using PTX and S-1 is promising for the prevention of peritoneal dissemination of T3/T4 advanced gastric cancer following R0 resection.…”
Section: Discussionsupporting
confidence: 72%
“…The other patient, given 80 mg/m 2 of PTX, had serum PTX levels measured 168 h after PTX administration. In these two patient's, the plasma levels of PTX remained within the effective range for 60 and 72 h respectively [20]. These results together with those cited above [7,9,10], suggest that sequential chemotherapy using PTX and S-1 is promising for the prevention of peritoneal dissemination of T3/T4 advanced gastric cancer following R0 resection.…”
Section: Discussionsupporting
confidence: 72%
“…The minimally effective plasma paclitaxel concentration in patients is reported to be 100 nM (Sekine et al, 1996;Malingre et al, 2001;Mross et al, 2006;Kobayashi et al, 2006). Both 100 and 7 nM paclitaxel concentrations were analyzed but only immunofluorescence data from cells treated with 100 nM paclitaxel were shown.…”
Section: Discussionmentioning
confidence: 99%
“…In case studies, complete disappearance of gastric ascites was reported to have been brought n, number of patients; C, cisplatin; U, UFT; F, 5-FU; L, folinic acid (LV); P, paclitaxel; S, S-1; 5′DFUR, doxifl uridine; RR, response rate; NR, not reported about by treatment with weekly [66] and biweekly [67] paclitaxel plus either S-1 or doxifl uridine [68]. Two pharmacokinetic studies demonstrated that the paclitaxel concentration in ascites remained within the optimal effective level for 72 h after intravenous administration [69,70]. In two clinical trials, the effi cacy of second-line paclitaxel or paclitaxel-containing regimens against gastric ascites was examined in patients whose disease had been refractory to fl uorinated pyrimidine therapy.…”
Section: Paclitaxel Chemotherapy For Peritoneal Dissemination and Ascmentioning
confidence: 99%